OPTIMIZATION OF SEPARATION AND PURIFICATION OF ETHANOL FROM HIGH-FRUCTOSE CORN SYRUP (HFCS) FERMENTATION BY SACCHAROMYCES CEREVISIAE - Huda Arrahman, Naufal
The demand for ethanol has significantly increased since the COVID-19 pandemic. Bio-ethanol production is typically conducted through the fermentation of biological substrates or biomass rich in simple carbohydrates, with Saccharomyces cerevisiae as the primary microorganism due to its efficiency in converting sugars to ethanol. To reduce production costs, High Fructose Corn Syrup (HFCS) is an ideal raw material due to its abundant glucose and fructose content. Optimizing downstream processes such as separation and purification is essential to maximize ethanol productivity and quality. This study focuses on fermentation and optimization of centrifugation, distillation, and alcohol drying processes, as well as mass balance analysis for the entire process. The results indicate that the optimal hydraulic retention time in the centrifuge is 20 minutes at a speed of 14,800 RCF. Optimal distillation conditions were achieved at a temperature of 60°C and a pressure of 134 mBar. The most effective alcohol drying was performed with a mass ratio of 1:1 between the adsorbent and water in the azeotropic mixture. From the overall process, ethanol purity reached 56.55%. Mass balance analysis showed an overall yield of 18.62% with ethanol purity at 100%.